Bibliometric Analysis of the Trend of Sociology of Communication Research Topics - Agustina Multi Purnomo (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Bibliometric analysis can provide extensive data mapping of previous research topic trends to formulate subsequent research topics. There is still a lack of bibliometric analysis of trends in sociology of communication research topics. The study used bibliometric analysis of 37,999 publications in ScienceDirect over three periods. Publication data was selected using the keyword "sociology of communication." Data processing was conducted by co-occurrence between keywords and data presentation with overlay visualization. The results of data processing with VosViewer revealed shifts in research topics over three periods. Topics that emerged after 2022 are related to Covid-19 pandemic, such as healthcare, resilience, stress, and vaccine hesitancy; methodologies like systematic literature review; recent technologies such as artificial intelligence; and other societal concerns, including sustainability. That topic was suggested for future research. However, sustainability and systematic literature review are old issues in other research fields. The research found that the sociology of communication research topics is changing dynamically and is influenced by social phenomena such as pandemics and technological advancements. The presence of two recent topics that have become old issues in other fields of social research shows the challenge for communication scientists to respond responsively to global social and methodological issues.